(untitled) (Research, Society and Development, 2022)
The action of plants, their phenoes and bioactives have been the target of intense scientific investigation, constituting an important source of new drugs for nowadays. The objective of this work was to evaluate the interactive antimicrobial activity, in vitro, of the extracts of the organic cultivation of acerola, Malphigia emarginata, against the standard strains Staphylococcus aureus CLITS 2275 FIOCRUZ, and Escherichia coli CLIST 3862 FIOCRUZ. For this, physicochemical analysis was performed. The results revealed that the tested extracts of acerola in two states of maturation, green and ripe, presented activity against the strains of S. aureus and E. coli, with average inhibition halos of 9.7 and 9.5 mm for ripe; and 11.15 and 10.67 mm for green; compared with the positive control, ethyl alcohol at 96%. The antimicrobial activity was similar, as there was no significant difference (p < 0.05). In the physicochemical analyses the green and ripe extracts were used, along with their inputs, among the extracts the pH was between 4.07 and 5.23; soluble solids 0.80 to 0.92 %, citric acid content 1.40 to 1.43 %; in reducing sugars 2.29 to 8.92 %, in ascorbic acid (mg/100g) ranged between 2491.30 and 3406.34. In this way, the use of the extracts of this study deserves a very careful look for the possibility of a directive action, opening a margin for both the analysis of the strains and the physicochemical data obtained, thus being a possible medium for the elaboration of drugs.